Perancangan Modul Training Pegawai di Departemen Blow Molding dan Injection Molding pada Perusahaan Kemasan Plastik - Gisella Gisella; Prayonne Adi (Jurnal Titra, 2020)
The problem in checking products is so many workers that make mistakes at inspections product. The type of blow molding product defect that many worker error inspections are scratch. The type of injection molding product defect is difficult to inspect are color defects and deformation. The root problem made after knew the problem. The root problem of checking products is domination by man factors and method factors. The root problem of checking products was implement in the training module. The training module made using the Best Training Practice guidelines, where the training methods used to meet the competency needs of workers' performance to be more efficient. The training module created modules, tasks, and tests. The module material consists of four parts, defects definition, causes of defects, defect classification, and types of product defects. The task in the module is to identify reject and accept goods also be able to use, read, and understand worker aids. Tests used are pretest, posttest, and practical test.